Holding specific views with humility: Conceptualization and measurement of specific intellectual humility. (July 2016) - Hoyle, Rick H.; Davisson, Erin K.; Diebels, Kate J.; Leary, Mark R.
Abstract: Although significant progress has been made in the conceptualization and measurement of intellectual humility, little is known about intellectual humility with respect to specific opinions, beliefs, and positions. We offer a conceptualization of specific intellectual humility and present three studies that examine its key tenets. Study 1 developed the Specific Intellectual Humility Scale and showed that its psychometric properties are excellent and invariant across a range of specific views. Study 2 considered additional specific views, further establishing measurement invariance and providing evidence of convergent and discriminant validity. Study 3 broadened the range of specific views and revealed that intellectual humility with respect to a specific view is a complex function of dispositional intellectual humility, the extremity of the view, and the basis for the view. These findings demonstrate the value of investigating intellectual humility with respect to specific views and the usefulness of the Specific Intellectual Humility Scale. Highlights: People may hold different beliefs with more or less humility. Specific intellectual humility is related to but different from general intellectual humility. A flexible measure of specific intellectual humility is developed and validated.